Menjadi Katalisator Perubahan: Kepemimpinan Karismatik Yang Membentuk Inovasi Organisasi Di Lingkungan Perusahaan - Simarmata, Anugrah Parsaulian; Rafly, Muhammad; Juliana, Chantika; Manalu, Bintang Try Anastasya; Wijaya, Muhammad Adhimawan (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
Charismatic leadership has emerged as a significant force in shaping innovation culture and driving change in today's dynamic business environment. The author investigates the role of charismatic leadership in shaping organizational innovation within the context of Company XYZ. Using a qualitative approach and case studies, the author gains deep insights into how characteristics of charismatic leadership, such as inspiration, vision, empowerment, and effective communication, contribute to the development of a strong innovation culture. Through data collection from in-depth interviews, participatory observation, and document analysis, the author identifies that charismatic leaders in Company XYZ are able to inspire employees, empower them to actively participate in the innovation process, and build strong relationships through effective communication. However, challenges such as expectation management, leadership capacity development, and appropriate reward systems still need to be addressed. The author's conclusion highlights the importance of strengthening and developing charismatic leadership within organizations as an effective catalyst for change and innovation to achieve quality organizational goals. Thus, this research provides valuable insights for management practitioners and organizational leaders interested in enhancing the quality of leadership and innovation culture in the modern business environment.